Implications des accords de Marrakech et de l'élargissement de l'Union Européenne sur les exportations agricoles marocaines - Ferdous C. (The GATT and Mediterranean agricultural trade, 1997)
Morocco is one of the principal extra-community providers of the European Union of fruit and vegetables. This sector of exportation, which contributes to height of 16 per cent in Moroccan total exports, represents a socio-economic stake of first importance. Vis-a-vis to the protectionist mechanisms of the CAP, Morocco made an effort of significant investment to adapt its offer in terms of calendar of export, quality and widening of the exported line of goods. In its offer with GATT, the European Union refitted the mechanisms of the CAP to make them in conformity with the provisions of the Final Act. However, the new mechanism negotiated with GATT institutes a level of protection often higher compared to the old system. The author examines here the foreseeable impacts on the one-hand conclusions of Uruguay round and on the other hand, widening of the UE on Moroccan exports.
Séminaire sur 'Le GATT et les Echanges Agricoles Méditerranéens', 1995/12/03-05, Chania (Greece)